Isotope composition (d18O and dD) of buried firn on the Lens and Amga river plain - V. B. Spektor; E. O. Dubinina; V. V. Spektor; N. T. Bakulina (Лëд и снег, 2015)
Layers of firn related to Karga (MIS 3) and Zyryan (MIS 4) horizons of Late Pleistocene were recovered in the permafrost stratum of Central Yakutia. Imaging points of δ¹⁸O and δD values characterizing the firn horizons are grouping near the line of meteoric water (Craig line). The firn was probably formed from permanent snow patches. The formation of permanent snow patches doesn’t occur at the present time due to climatic reasons – exceeding of evaporation over precipitation as well as high summer temperatures. We suppose that formation of the firn occurred in conditions different from the modern ones, under lower mean annual temperatures and higher humidity.